Assessing the hepatoprotective efficacy of Vitis gracilis Wall. against doxorubicin-induced hepatic injury in rats - Yurnadi Hanafi Midoen; Syafruddin Ilyas; Putra Santoso (GarVal Editorial Ltda., 2024)
Context: Doxorubicin is an anticancer drug that can adversely affect the liver. Therefore, seeking medical attention to manage pain and minimize side effects is crucial. Aims: To evaluate the hepatoprotective potential of Vitis gracilis Wall. nanoherbs against doxorubicin-induced hepatotoxicity. Methods: The study included five treatment groups: T0 (negative control), T+ (positive control with doxorubicin alone), TC (doxorubicin + vitamin C at 0.2 mg/kg body weight/day), T125 (doxorubicin + V. gracilis at 125 mg/kg body weight/day), and T150 (doxorubicin + V. gracilis at 150 mg/kg body weight/day). Doxorubicin, administered intraperitoneally at 0.0019 mg/kg body weight once a week for three weeks, induced hepatotoxicity in the T+ group. Results: Serum transaminases were significantly reduced in the T125 and T150 groups, indicative of the hepatoprotective effects of V. gracilis. Immunohistochemical analysis demonstrated the modulation of key markers, with decreased levels of pro-inflammatory tumor necrosis factor-α and increased levels of anti-inflammatory interleukin 10 in the T125 and T150 groups. The activities of oxidative stress markers, including superoxide dismutase and caspase 3, were favorably influenced by V. gracilis nanoherb treatment. Conclusions: These findings suggest that V. gracilis nanoherbs may effectively attenuate doxorubicin-induced hepatotoxicity, evidenced by biochemical and immunohistochemical changes. This study provides a foundation for further exploration of V. gracilis nanoherbs as a potential adjunctive therapy in preventing chemotherapy-associated liver damage.